Determining cantilever stiffness from thermal noise - Lübbe, Jannis; Temmen, Matthias; Rahe, Philipp; Kühnle, Angelika; Reichling, Michael (Beilstein Journal of Nanotechnology, 2013)
We critically discuss the extraction of intrinsic cantilever properties, namely eigenfrequency fn, quality factor Qn and specifically the stiffness kn of the nth cantilever oscillation mode from thermal noise by an analysis of the power spectral density of displacement fluctuations of the cantilever in contact with a thermal bath. The practical applicability of this approach is demonstrated for several cantilevers with eigenfrequencies ranging from 50 kHz to 2 MHz. As such an analysis requires a sophisticated spectral analysis, we introduce a new method to determine kn from a spectral analysis of the demodulated oscillation signal of the excited cantilever that can be performed in the frequency range of 10 Hz to 1 kHz regardless of the eigenfrequency of the cantilever. We demonstrate that the latter method is in particular useful for noncontact atomic force microscopy (NC-AFM) where the required simple instrumentation for spectral analysis is available in most experimental systems.
Keywords: AFM; cantilever; noncontact atomic force microscopy (NC-AFM); Q-factor; thermal excitation; resonance; spectral analysis; stiffness